Problematic smartphone use relationship with pathological personality traits: Systematic review and meta-analysis - Lucas F. Carvalho; Catarina P. Sette; Bárbara Letícia Ferrari (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2018)
The present study aimed to investigate relationships between problematic use of smartphone and pathological personality traits. To do so, we performed a systematic review and meta-analysis when sufficient information was presented. The literature search was conducted based on a search strategy including the keywords “smartphone” and “personality”. Variations were not included as we seek to increase the breadth of the search. Random effects models were used to generate standardized coefficient for meta-analysis. In total, the present study included 5 papers covering 6.096 participants. Our findings indicated a scarcity of studies meeting the criteria used, but evidence regarding the relationship between problematic use of smartphone and neuroticism and impulsivity traits were found. Meta-analysis using levels of problematic use of smartphone and neuroticism and impulsivity measures showed a significant and small to moderate effect size, with an observed heterogeneity (I2) equal to 97.26% (impulsivity) and 58.89% (neuroticism). More research should be carried out in the area, allowing the accumulation of evidence considering several personality pathological traits. The impulsivity and neuroticism traits should be further investigated, including studies with psychiatric samples. Future studies should seek to establish a standard for study design and assessment tools to be used.